2017
DOI: 10.1016/j.ssmph.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The risk of female genital cutting in Europe: Comparing immigrant attitudes toward uncut girls with attitudes in a practicing country

Abstract: Worldwide, an estimated 200 million girls and women have been subjected to female genital cutting. Female genital cutting is defined as an intentional injury to the female genitalia without medical justification. The practice occurs in at least 29 countries in Africa, the Middle East, and Asia. In addition, globalization and migration have brought immigrants from countries where cutting is commonly practiced to countries where cutting is not traditionally practiced and may even be illegal. In countries receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 37 publications
4
65
0
Order By: Relevance
“…Involves systems development, using a cyclical and iterative process. 8. Disseminates results to all partners and involves them in the wider dissemination of results.…”
Section: Element 2: Understanding the Social Norm Perpetuating Fgmmentioning
confidence: 99%
See 2 more Smart Citations
“…Involves systems development, using a cyclical and iterative process. 8. Disseminates results to all partners and involves them in the wider dissemination of results.…”
Section: Element 2: Understanding the Social Norm Perpetuating Fgmmentioning
confidence: 99%
“…It had become an identity marker. This contradictory evidence of the impact of migration on the practice of FGM could be explained by migration selection, including ethnicity and lineage, as well as education, poverty and urbanization levels [13] together with the intensity of acculturation [8] in different countries and by different FGM affected groups. It is a situation in flux and more research is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diaspora, some of these traditional values are changing. Several studies have found increasingly negative attitudes to infibulation (Gele et al, 2012;Johansen, 2017aJohansen, , 2019Johnsdotter & Essèn, 2016;Mestre i Mestre & Johnsdotter, 2019;Vogt, Efferson, & Fehr, 2017;Wahlberg, Johnsdotter, Selling, Källestål, & Essén 2017) and some acceptance of surgical deinfibulation (Tvenge & Andersen, 2017). Nevertheless, there remains substantial resistance to deinfibulation.…”
Section: Infibulation As a Cultural Practicementioning
confidence: 99%
“…A growing number of studies show that migration seems to be a key factor for change when it comes to attitudes and practices regarding circumcision of girls among Africans in Europe. [7][8][9][10][11][12][13][14][15][16] Some 200,000 people who were born in Africa live in Sweden. The biggest community is the Somalipersons born in Somalia amount to more than 66,000.…”
Section: Circumcision Of Girls Residing In Europementioning
confidence: 99%